2001
DOI: 10.1007/bf02234833
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic production of prolactin by colorectal adenocarcinoma

Abstract: These multiple approaches confirmed that prolactin is produced by colorectal carcinoma cells. Looking at its prognostic value and correlation with disease activity, it may provide new insights into treatment for patients with colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 15 publications
1
39
0
1
Order By: Relevance
“…Ectopic production is commonly seen in several tumor types. It has been observed that PRL and HGH are produced by tongue tumors [12] , and colorectal carcinoma cells [13] . Ectopically produced PRL may act as a major local growth promoter via autocrine and paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic production is commonly seen in several tumor types. It has been observed that PRL and HGH are produced by tongue tumors [12] , and colorectal carcinoma cells [13] . Ectopically produced PRL may act as a major local growth promoter via autocrine and paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The first study assessed prolactin receptor protein by radioligand assay using 125 I-hGH. Tumor specimens of 71 male patients were analyzed and prolactin receptor was found to be positive in 36 (51%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study, the same group of authors noted prolactin receptor immunoreactivity in 26 out of 56 (46%) tumors. 19 The authors used a monoclonal mouse anti-human prolactin receptor antibody different from the one used in our study, which may have accounted for the low prevalence of prolactin receptor expression. Data were not correlated with follow-up in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic production is commonly seen in several tumor types. It has been observed that PRL and HGH are produced by tongue tumors [105], and colorectal carcinoma cells [106]. Ectopically produced PRL may act as a major local growth promoter via autocrine and paracrine mechanisms.…”
Section: Discussionmentioning
confidence: 99%